Systematic-Linguistic Description of Hippological Lexicon in English and Uzbek and Creation of an Electronic Bilingual Hippological Dictionary - Abdinazarov , Oktam Qushoqovich (The Lingua Spectrum, 2026)
This article addresses the inadequacy of bilingual resources for hippological terminology in English and Uzbek by systematically analyzing and comparing the hippological lexicon of both languages. The research identifies key terminologies, explores semantic discrepancies, and examines the cultural contexts that shape language use in this specialized field. Employing a mixed-methods approach, the study integrates qualitative linguistic analysis with quantitative data on the frequency and usage patterns of words drawn from diverse texts. The findings reveal notable differences in terminology and conceptualization, as well as the influence of cultural factors on language related to equestrian practices. The creation of an electronic bilingual hippological dictionary emerges as a significant outcome, serving as a vital resource for professionals in healthcare and veterinary medicine engaged with equine therapy and equestrian-related health issues. Furthermore, this resource has the potential to support academic research and education in the field of hippology, bridging gaps between theory and practice. It also encourages the standardization of terminology, facilitating clearer communication among specialists across different linguistic and cultural contexts.